Prospects of enacting the economic productivity policy in the Republic of Armenia - Mariam A. Voskanyan (Journal of New Economy)
Global economic and geopolitical changes play up the profound significance of choosing a macroeconomic regulation approach. Adverse impact of external shocks cannot be eliminated solely by short-term mechanisms traditionally utilised by governments in times of crisis. Only economies that adopt a macroeconomic policy of increasing the economic productivity are able to earn stability. The paper is intent to assess the potential of Armenia’s economy in terms of applying a macroeconomic regulation approach consisting in increasing the economic productivity. The postulates of the classic theory of economic growth and the concept of economic productivity constitute the methodological basis of the research. The methods include times series and comparative analysis, generalisation and synthesis. The evidence is the statistical data on Armenia’s economy, as well as the dynamics of international indices and rankings from 1990 to 2023. The findings demonstrate that the major factors in raising Armenia’s economic productivity are innovation potential and human capital. Strengthening these advantages can produce a positive effect on the country’s economic growth and development both in the short and long run, which supports the necessity to reconsider the thrusts of Armenia’s macroeconomic policy.